ChemInform Abstract: 2‐D and 3‐D Phosphotungstate‐Based TM—Ln Heterometallic Derivatives Constructed from Dimeric [Ln(α‐PW11O39)2]11‐ Fragments and Copper‐Organic Complex Linkers. Issue 4 (31st January 2013) - Shang, Sensen; Zhao, Junwei; Chen, Lijuan; Li, Yuye; Zhang, Jingli; Li, Yanzhou; Niu, Jingyang
Abstract Compounds (IV), (VI), and (VIII) are characterized by powder and single crystal XRD, IR and optical diffuse reflectance spectroscopy, magnetic measurements, and luminescence spectroscopy.